2018
DOI: 10.1111/bjet.12618
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the flipped learning pre‐class: Its influence on the success of flipped learning and related factors

Abstract: Flipped learning (FL) has had a substantial impact on higher education worldwide, prompting active dialog among educational researchers and practitioners. It is widely accepted that the value of FL lies in enabling in‐depth, learner‐centered learning experiences by offloading content delivery onto pre‐class online learning. The in‐class component is thus generally considered more critical, even though both pre‐class and in‐class elements are indispensable components of FL and practitioners are faced with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 19 publications
3
70
0
3
Order By: Relevance
“…This is more obvious among learners with low prior knowledge (LPK) than those with high prior knowledge (HPK; Mayer, ). Even the few studies that referred to CTML in FCA did not use its principles to design educational multimedia or compare learners' academic achievements for HPK with LPK (Lee & Choi, ; Lento, ; Slemmons et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is more obvious among learners with low prior knowledge (LPK) than those with high prior knowledge (HPK; Mayer, ). Even the few studies that referred to CTML in FCA did not use its principles to design educational multimedia or compare learners' academic achievements for HPK with LPK (Lee & Choi, ; Lento, ; Slemmons et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Student engagement provides an engaged environment which facilitates the achievement of learning outcomes (Brame, 2013) where the teaching style matches the students' learning style. Flipped classroom focuses on learner centered delivery style (Gilboy et al, 2015;Lee & Choi, 2018) and enhances student engagement (Tucker, 2012) which deepens the understanding of the subject (Klem & Connell, 2004). Flipped classroom facilitates constant monitoring and interaction with the teachers (Stone, 2012) for better student engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Flipped classroom is an innovative pedagogical approach that focuses on learner centered delivery style (Gilboy et al, 2015;Sivarajah, Curci, Johnson, Lam, Lee & Richardson, 2018;Lee & Choi, 2018) and enhances student engagement (Tucker, 2012) which has always been a challenge for educators (Klem & Connell, 2004). Flipped classrooms transform the roles of teachers and students, and compel the teachers to come up with new plans (Jinlei, Ying & Baohui, 2012).…”
Section: Student Engagementmentioning
confidence: 99%
“…Second, students' autonomy is also affected by the degree to which students can manipulate the pace and sequencing (e.g., pause and rewind the instructional videos) of the learning content (Abeysekera & Dawson, 2015;Van Laer & Elen, 2017), but also in their decision where (environmental structuring) and when (planning) to learn (Jansen et al, 2018). Consequently, when students are able to regulate their own learning adequately, they achieve higher learning outcomes in FL in contrast to students who are less able to regulate their own learning (Lai & Hwang, 2016;Lee & Choi, 2019;Shibukawa & Taguchi, 2019). Students with lesser SRL skills could show ineffective study behavior when they are given more autonomy.…”
Section: Flipped Learning Demands More Self-regulated Learning Behavimentioning
confidence: 99%
“…In the theoretical model we use, SRL is presented as a cyclic model in which three phases (forethought, performance, self-reflection) are distinguished and learners apply metacognitive strategies such as goal setting and planning in the forethought phase, monitoring and self-control in the performance phase, and evaluation and adaption in the self-reflection phase (Zimmerman & Moylan, 2009). SRL is a relevant addition to current research on FL, as a flipped classroom places a strong demand on students' SRL skills (He et al, 2016) and self-directness (Lee & Choi, 2019) when studying outside the classroom. First, general meta-analytical research on SRL has shown that supporting SRL in primary and secondary education resulted in better learning outcomes (Dent & Koenka, 2016;Dignath & Büttner, 2008;Donker et al, 2014).…”
Section: Self-regulated Learning In Flipped Classrooms: Theoretical Pmentioning
confidence: 99%